Analisis Pemakaian Aizuchi Pada Novel Gakko No Sensei Karya Komatsu Eriko - Setiawati, Nia (Kagami : Jurnal Pendidikan dan Bahasa Jepang, 2012)
This paper is a research report about the type and function of aizuchi in the novel Gakko no Sensei by Eriko Komatsu. Aizuchi is expression for the other person replied talks. Aizuchi usage in a communication can not be taken lightly because the conversation without aizuchi can lead to misunderstandings between the speaker and the listener. Aizuchi usage will be very important especially when communicating without dealing directly with the speaker, for example via telephone conversations.The author conducted research on aizuchi contained on a novel by Eriko Komatsu to determine the type and function of aizuchi. Based on the analysis, it is known that the type of aizuchi contained in the novel Gakko no Sensei by Eriko Komatsu consists “Hai, Un, Haa, Ee, E, Hee, Naruhodo, Soudesuka/Souka/Sou/Souyara, Soudesune/Soune/Souyone/Soudane, Hontou, Uso.” The function of aizuchi which contained in the novel is classified as follows: 1.Aizuchi stating an affirmation, 2.Aizuchi to ensure approval, 3. Aizuchi which state of denial.This research is expected to provide input for Japanese language teachers and learners on the correct and appropiate aizuchi usage. Also expected to become an input for the course Kaiwa and Bijinesu Kaiwa because errors in the aizuchi usage can lead to unharmonious relationships between the listener and the speaker.